2006
DOI: 10.1287/ited.7.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Spreadsheet Engineering in a Management Science Course: A Hierarchical Approach

Abstract: Business students who rely on spreadsheets can use management science only to the extent that they can build a spreadsheet model of an unstructured business situation. Spreadsheets are the primary vehicle for analytical work in business, are advantageous for modeling and model representation, and are used by management science practitioners as well as end-user modelers. There is a common misperception that spreadsheets are somehow "easy" to use. However, the spreadsheet is a powerful rapid development computer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Black et al 2005;Dembeck and Stout 1997;Hwarng 2001;Grossman 2006;Lilien et al 1998;Markham and Palocksay 2006;Palocksay and Markham 2002;Sosin et al 2004;Yi and Davis 2003). Sosin et al (2004) examine the use of technology (including spreadsheets) in economics education.…”
Section: Extant Literature: Spreadsheet In Business Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…Black et al 2005;Dembeck and Stout 1997;Hwarng 2001;Grossman 2006;Lilien et al 1998;Markham and Palocksay 2006;Palocksay and Markham 2002;Sosin et al 2004;Yi and Davis 2003). Sosin et al (2004) examine the use of technology (including spreadsheets) in economics education.…”
Section: Extant Literature: Spreadsheet In Business Educationmentioning
confidence: 99%
“…Hwarng (2001) employs a simulation in his course that uses the spreadsheet as a platform to teach student the nuances of simulation models. Grossman (2006) describes the process of spreadsheet engineering in a management science course. These examples illustrate the extensive use of spreadsheet for teaching and training purposes, primarily in OR/MS, decision sciences and MIS areas, with a focus on teaching the intricacies of the spreadsheet.…”
Section: Extant Literature: Spreadsheet In Business Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…to fix student spreadsheet deficiencies with minimal use of class time using "student-led remediation" described in Grossman (2006). Students need to be able to use the INDEX function to program the Scenario Engine and Excel's Data Table tool to build the scenario summary report.…”
Section: Figure 15mentioning
confidence: 99%
“…In the 1990s, the use of spreadsheets for data management and problem formulation and solution increased dramatically (Erickson and Turban 1985, Jones 1986, Winston 1996, Conway and Ragsdale 1997, Martin 2000. The next innovation focused spreadsheet capabilities on business decision models and the use of management science in these models (Bodily 1996, Mather 1999, Powell 2000, Robinson et al 2003, Sokol 2005, Grossman 2006). Leong and Cheong (2008), for example, suggested that a separate course in business modeling be taken before the course in management science.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%